2015
DOI: 10.1111/j.1540-4781.2015.12179.x
|View full text |Cite
|
Sign up to set email alerts
|

Universal Development and L1–L2 Convergence in Bilingual Construal of Manner in Speech and Gesture in Mandarin, Japanese, and English

Abstract: This article investigates bilingual versus monolingual construal of manner of motion in speech and gesture across three languages—Mandarin, Japanese, and English—argued to be typologically distinct in speech and co‐speech gesture (Brown & Chen, 2013; McNeill, 2001; Slobin, 2004b; Talmy, 1991). Narrative descriptions of motion were elicited in the L1 and L2 from bilingual Mandarin–English (n = 12) and Japanese–English (n = 15) speakers at an intermediate, CEFR–B level of L2 proficiency, and from monolingual spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 76 publications
7
53
1
Order By: Relevance
“…A growing number of studies on language, cognition, and thinkingfor-speaking have also analyzed how path and/or manner of motion is conveyed through gesture in motion events (Brown 2015;Hendriks and Hickmann 2015;Brown and Gullberg 2008;Choi and Lantolf 2008;Chui 2011;Gullberg et al 2008;McNeill, 2001;Özyürek, et al 2008;Pavlenko and Volynski 2015). Specifically, McNeill and Duncan (2000), Negueruela et al (2004), and Stam (2006Stam ( , 2010Stam ( , 2015 draw attention to the different ways in which Spanish and English speakers gesticulate with motion events.…”
Section: Sociocultural Theory Gesturing and Motion Eventsmentioning
confidence: 98%
“…A growing number of studies on language, cognition, and thinkingfor-speaking have also analyzed how path and/or manner of motion is conveyed through gesture in motion events (Brown 2015;Hendriks and Hickmann 2015;Brown and Gullberg 2008;Choi and Lantolf 2008;Chui 2011;Gullberg et al 2008;McNeill, 2001;Özyürek, et al 2008;Pavlenko and Volynski 2015). Specifically, McNeill and Duncan (2000), Negueruela et al (2004), and Stam (2006Stam ( , 2010Stam ( , 2015 draw attention to the different ways in which Spanish and English speakers gesticulate with motion events.…”
Section: Sociocultural Theory Gesturing and Motion Eventsmentioning
confidence: 98%
“…Some of the studies concern foreign language learners who have different uses and exposures to the target language and exhibit proficiency levels ranging from beginner to advanced. The L1–L2 pairs represented among these specific studies are Chinese/Mandarin–English (Brown, ), English–French (Hendriks & Hickmann, 2015), English–German (Athanasopoulos et al, ), Japanese–English (Brown), Polish–English (Tomczak & Ewert, 2015), and Swedish–English (Bylund & Athanasopoulos, 2015). The other studies deal with naturalistic/semi‐naturalistic learners immersed in the L2 environment, with different ages of L2 acquisition and different lengths of L2 exposure.…”
Section: The Current Special Issuementioning
confidence: 99%
“…Brown (), looking at the expression of manner in Japanese and Chinese learners of English, illustrates the importance of multimodal approaches to understanding learner languages. In contrast to what is commonly assumed (e.g., Slobin, ), her findings on manner expression in speech and gesture show that L1 patterns are susceptible to restructuring, even at moderate levels of L2 proficiency.…”
Section: The Current Special Issuementioning
confidence: 99%
“…Stam () examined the use of path in both speech and co‐speech gestures by Spanish‐speaking learners of L2 English (5 intermediate vs. 5 advanced learners based on program level). Her study found that the learners’ speech–gesture patterns did not completely align with those of either the L1 or L2 (see also Brown, ; Brown & Gullberg, ). In another study by Choi and Lantolf () with 9 participants, they also suggested that the learners preferred to retain their L1 TFS in their L2 gesture production, even though the learners were at an advanced level of the L2.…”
Section: Introductionmentioning
confidence: 99%
“…According to Slobin's thinking‐for‐speaking (TFS) hypothesis (, , ), when acquiring a language, children gradually become attuned to different aspects of motion events that are readily codable in the language, so as to develop language‐particular TFS patterns. Second language (L2) and bilingual research has begun to look into the issue of whether and how adult L2 learners or late bilinguals come to develop target‐like TFS patterns (e.g., Brown, ; Brown & Gullberg, ; Cadierno, , , ; Choi & Lantolf, ; Han & Cadierno, ; Lai, Rodriguez, & Narasimhan, ; Wu, ).…”
mentioning
confidence: 99%